Creating E-Comic to Motivate Students to Learning Mandarin - Chandra, Mei Rianto; Kun, Qian; Ying, Yi; Tanoto, Florence Y; Mufida, Ziola A (Lingua Cultura, 2024)
The research explored whether digital comic books were a new learning method that could increase learning motivation in learning Mandarin. Illustrated learning media made it easier for students to understand learning material. Along with the times and technological advances, learning methods had also developed in various ways. The questions in the research were: (1) How was the application of e-comic in learning Mandarin?; (2) What did students think about learning with e-comic? The research applied a qualitative method, and 40 students who studied Mandarin were the respondents. Based on the results, it can be concluded that all respondents agree that applying learning media using digital comic books can provide positive results in learning Mandarin. All respondents think learning through e-comic makes it easier to understand grammatical material and helps compose sentences to construct conversations. Learning with comic book media is considered very interesting. Even though the learning process using comic book media occurs online during the pandemic, learning with comic book media can create interactive learning. Students can become more creative and able to use various applications to make their own comics with the characters they choose. Learning with comic books can motivate students to learn Mandarin.